Le recul de l'emploi manufacturier privé en Tunisie : analyse de la région du littoral sur la période post-révolution (2011-2016) - Nejib Chagour; Samia Haddad; Sébastien Bourdin (Territoire en Mouvement)
The objective of the article is to analyze the new stylized facts related to the Tunisian revolution (loss of competitiveness, deindustrialization and reallocation of employment between sectors) which affected private manufacturing industries, more particularly those located in the coastal region. Based on the regional growth model, we identify the determinants of the (decrease) increase of manufacturing employment in the Tunisian coastal region using an unbalanced panel of 14 sectors spread over 150 delegations of 12 coastal governorates. The results show that industrial specialization, the initial size of establishments, the initial size of delegations, the average salary, the proportion of the population aged 10 years and over with a primary level have a negative effect on employment growth. In contrast, industrial diversity is a factor in employment growth. A delegation endowed with a qualified workforce stimulates its growth. The results also show that a phenomenon of job reallocation determines the growth of sectors. Finally, a process of regional convergence was recorded in the delegations of the Center-East as well as a remarkable effect of the decentralization policies on the growth of the delegations of the governorate of Zaghouan and Manouba.